Excessive Daytime Sleepiness in Tension-Type Headache: A Population Study - Kim, Kyung Min; Kim, Jiyoung; Cho, Soo-Jin; Kim, Won-Joo; Yang, Kwang Ik; Yun, Chang-Ho; Chu, Min Kyung (Frontiers in Neurology, 2019)
Excessive daytime sleepiness (EDS) is a prevalent sleep-related complaint across the general population and has been reported to be associated with headache. Tension-type headache (TTH) is the most commonly encountered headache and accounts for a significant amount of disease burden. However, the association between EDS and TTH is currently scarce. In the present study, we investigated the impact of EDS on the prevalence and clinical presentation of TTH. We utilized data from the Korean Headache-Sleep Study, a national survey that sought to identify headache and sleep characteristics in Korean adults. Participants with an Epworth sleepiness scale score greater or equal to 11 were considered as having EDS. Of the 2695 participants enrolled, 570 (21.2%) and 313 (11.6%) had TTH and EDS, respectively. EDS was highly prevalent in individuals with chronic tension-type headache (CTTH) than in those without headache (35.7% vs. 9.4%, p < 0.001). The prevalence of EDS in episodic tension-type headache (ETTH) individuals with a headache frequency < 1 per month (8.3%, p = 0.511) and ETTH individuals with a headache frequency of 1-14 per month (13.5%, p = 0.054) was not significantly different from that in individuals without headache (9.4%). TTH participants with EDS had a higher headache frequency per month (4.3 ± 8.1 vs. 1.7 ± 4.2, p = 0.013), more severe headache intensity (Visual Analogue Scale, 5.0 [3.0 – 6.0] vs. 4.0 [3.0 – 6.0], p = 0.008), a higher impact of headache (Headache Impact Test-6 score, 47.1 ± 7.3 vs. 43.5 ± 7.6, p < 0.001), and a higher prevalence of depression (12.7% vs. 3.2%, p < 0.001) than TTH participants without EDS. Consequently, CTTH is associated with higher EDS prevalence compared to ETTH and without headache. Moreover, TTH with EDS had more severe TTH symptoms compared to TTH without EDS.